Evaluation of the analyses of tert-butyldimethysilyl derivatives of naphthenic acids by gas cromatography-electron impact mass spectrometry - Clemente, Joyce S.; Fedorak, Philip M. (Journal of Chromatography A, 2004)
Naphthenic acids are a complex mixture of carboxylic acids with the general formula CnH(2n+Z)O2 and they are natural, toxic components of crude oils. GC-MS analyses of tert-butyldimethylsilyl esters of naphthenic acids are used to estimate component distribution within naphthenic acids mixtures. Our evaluations of the GC-MS method showed that ions from column bleed erroneously appear as C14 Z = -4 acids and that correcting for heavy isotopes of C and Si do not significantly affect ion distribution plots. Overall, the GC-MS method appears to overestimate the relative proportion of low-molecular-mass acids.
Keywords: analytical methodology; naphthenic acids; UofA